Chiara Lubich's "Resurrection of Rome". Reflections in Light of Special Psychopedagogy - Dorota Kornas-Biela (Nicolaus Copernicus University in Toruń, 2019)
The article undertakes a reflection on the significance of Chiara Lubich's text "The Resurrection of Rome" for special needs psychopedagogy. First, it responds to the question of the subject of this short "philosophical-theological thesis", i.e., what is the state of the contemporary human person, who observing "contemporary Rome" full of dirt, vanity and sin not only surrounding him or herself, but also within, simultaneously deciphers his or her destiny as being resurrection. Created in the likeness of God, the human person is free and called to free and joyful "gaining of Heaven" and to relationship with God. In the contemporary world, disability continues to be received as "bad" and a deprivation of the most important values; it draws negative social attitudes, and so it is important to offer a key to change this destructive attitude toward others. The second section of the article is devoted to an analysis of the suggestions which Ch. Lubich included in the text "The Resurrection of Rome", and which may be used in the process of changing attitudes towards people with disability. These suggestions correspond to the assumptions of Christian personalism in special needs education.